PENGARUH PENGGUNAAN LEMBAR KERJA SISWA (LKS) DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS SMA NEGERI 3 KOTA JAMBI - Sondang Purba; Diliza Afrila (SJEE (Scientific Journals of Economic Education), 2020)
This study aims to determine the effect of using Student Worksheets (LKS) and the independent learning outcomes of students in economic subjects in class X IPS SMA Negeri 3 Jambi City. The results showed that (1) the use of student worksheets (LKS) did not have a significant effect on student learning outcomes. Based on the results of data analysis, it is known that the value of tcount < ttable (1.441 <1.659). Furthermore, the variable contribution of using Student Worksheets (LKS) to student learning outcomes is 11.7%. (2) Independent learning has a significant effect on student learning outcomes. Based on the results of data analysis, it is known that the value of tcount > ttable (1.937 > 1.659). Furthermore, the contribution of the independent learning variable to student learning outcomes is 19.2%. (3) The use of student worksheets (LKS) and independent learning has a significant effect on student learning outcomes in economic subjects in class X IPS at SMA Negeri 3 Jambi City. Based on the results of data analysis, it is known that the value of Fcount > Ftable (3.166> 3.04). Furthermore, the variable contribution of the use of student worksheets (LKS) and independent learning to learning outcomes was 36.4%.